-- Because iterated products currently require both A and B to be of the same -- universe, and the FiniteMap is written in a universe-polymorphic way, -- specialize the FiniteMap module with Set-typed types only. open import Lattice open import Equivalence open import Relation.Binary.PropositionalEquality as Eq using (_≡_; refl; sym; trans; cong; subst) open import Relation.Binary.Definitions using (Decidable) open import Agda.Primitive using (Level) renaming (_⊔_ to _⊔ℓ_) open import Function.Definitions using (Inverseˡ; Inverseʳ) module Lattice.FiniteValueMap (A : Set) (B : Set) (_≈₂_ : B → B → Set) (_⊔₂_ : B → B → B) (_⊓₂_ : B → B → B) (≈-dec-A : Decidable (_≡_ {_} {A})) (lB : IsLattice B _≈₂_ _⊔₂_ _⊓₂_) where open import Data.List using (List; length; []; _∷_) open import Utils using (Unique; push; empty) open import Data.Product using (_,_) open import Data.List.Properties using (∷-injectiveʳ) open import Data.List.Relation.Unary.All using (All) open import Data.List.Relation.Unary.Any using (Any; here; there) open import Relation.Nullary using (¬_) open import Lattice.Map A B _≈₂_ _⊔₂_ _⊓₂_ ≈-dec-A lB using (subset-impl) open import Lattice.FiniteMap A B _≈₂_ _⊔₂_ _⊓₂_ ≈-dec-A lB public module IterProdIsomorphism where open import Data.Unit using (⊤; tt) open import Lattice.Unit using () renaming (_≈_ to _≈ᵘ_; _⊔_ to _⊔ᵘ_; _⊓_ to _⊓ᵘ_; ≈-dec to ≈ᵘ-dec; isLattice to isLatticeᵘ) open import Lattice.IterProd _≈₂_ _≈ᵘ_ _⊔₂_ _⊔ᵘ_ _⊓₂_ _⊓ᵘ_ lB isLatticeᵘ as IP using (IterProd) from : ∀ {ks : List A} → FiniteMap ks → IterProd (length ks) from {[]} (([] , _) , _) = tt from {k ∷ ks'} (((k' , v) ∷ kvs' , push _ uks') , refl) = (v , from ((kvs' , uks'), refl)) to : ∀ {ks : List A} → Unique ks → IterProd (length ks) → FiniteMap ks to {[]} _ ⊤ = (([] , empty) , refl) to {k ∷ ks'} (push k≢ks' uks') (v , rest) with to uks' rest ... | ((kvs' , ukvs') , kvs'≡ks') = let -- This would be easier if we pattern matched on the equiality proof -- to get refl, but that makes it harder to reason about 'to' when -- the arguments are not known to be refl. k≢kvs' = subst (λ ks → All (λ k' → ¬ k ≡ k') ks) (sym kvs'≡ks') k≢ks' kvs≡ks = cong (k ∷_) kvs'≡ks' in (((k , v) ∷ kvs' , push k≢kvs' ukvs') , kvs≡ks) private _≈ᵐ_ : ∀ {ks : List A} → FiniteMap ks → FiniteMap ks → Set _≈ᵐ_ {ks} = _≈_ ks _≈ⁱᵖ_ : ∀ {ks : List A} → IterProd (length ks) → IterProd (length ks) → Set _≈ⁱᵖ_ {ks} = IP._≈_ (length ks) from-to-inverseˡ : ∀ {ks : List A} (uks : Unique ks) → Inverseˡ (_≈ᵐ_ {ks}) (_≈ⁱᵖ_ {ks}) (from {ks}) (to {ks} uks) -- from (to x) = x from-to-inverseˡ {[]} _ _ = IsEquivalence.≈-refl (IP.≈-equiv 0) from-to-inverseˡ {k ∷ ks'} (push k≢ks' uks') (v , rest) with ((kvs' , ukvs') , refl) ← to uks' rest in p rewrite sym p = (IsLattice.≈-refl lB , from-to-inverseˡ {ks'} uks' rest) -- the rewrite here is needed because the IH is in terms of `to uks' rest`, -- but we end up with the 'unpacked' form (kvs', ...). So, put it back -- in the 'packed' form after we've performed enough inspection -- to know we take the cons branch of `to`. -- The map has its own uniqueness proof, but the call to 'to' needs a standalone -- uniqueness proof too. Work with both proofs as needed to thread things through. from-to-inverseʳ : ∀ {ks : List A} (uks : Unique ks) → Inverseʳ (_≈ᵐ_ {ks}) (_≈ⁱᵖ_ {ks}) (from {ks}) (to {ks} uks) -- to (from x) = x from-to-inverseʳ {[]} _ (([] , empty) , kvs≡ks) rewrite kvs≡ks = ((λ k v ()) , (λ k v ())) from-to-inverseʳ {k ∷ ks'} uks@(push k≢ks'₁ uks'₁) fm₁@(m₁@((k , v) ∷ kvs'₁ , push k≢ks'₂ uks'₂) , refl) with to uks'₁ (from ((kvs'₁ , uks'₂) , refl)) | from-to-inverseʳ {ks'} uks'₁ ((kvs'₁ , uks'₂) , refl) ... | ((kvs'₂ , ukvs'₂) , _) | (kvs'₂⊆kvs'₁ , kvs'₁⊆kvs'₂) = (m₂⊆m₁ , m₁⊆m₂) where kvs₁ = (k , v) ∷ kvs'₁ kvs₂ = (k , v) ∷ kvs'₂ m₁⊆m₂ : subset-impl kvs₁ kvs₂ m₁⊆m₂ k' v' (here refl) = (v' , (IsLattice.≈-refl lB , here refl)) m₁⊆m₂ k' v' (there k',v'∈kvs'₁) = let (v'' , (v'≈v'' , k',v''∈kvs'₂)) = kvs'₁⊆kvs'₂ k' v' k',v'∈kvs'₁ in (v'' , (v'≈v'' , there k',v''∈kvs'₂)) m₂⊆m₁ : subset-impl kvs₂ kvs₁ m₂⊆m₁ k' v' (here refl) = (v' , (IsLattice.≈-refl lB , here refl)) m₂⊆m₁ k' v' (there k',v'∈kvs'₂) = let (v'' , (v'≈v'' , k',v''∈kvs'₁)) = kvs'₂⊆kvs'₁ k' v' k',v'∈kvs'₂ in (v'' , (v'≈v'' , there k',v''∈kvs'₁))